Catheter ablation supported by extracorporeal membrane oxygenation -last resort treatment of arrhythmic storm?. (14th October 2021) - Costa, C; Amador, F; Calvao, J; Pestana, G; Lebreiro, A; Pinto, R; Proenca, T; Carvalho, M; Pinho, T; Ferreira, A; Albuquerque-Roncon, R; Adao, L; et al.
Abstract: Introduction: Arrhythmic storm (AS) is associated with high mortality, even with best medical care and hemodynamic support. If medical therapeutic failure, electrophysiological mapping and ablation are potential lifesaving therapies. Venoarterial extracorporeal membrane oxygenation (VA-ECMO) provides temporary mechanical circulatory support and can be used as a salvage intervention in patients with cardiogenic shock. Considering the seriousness of AS and the technical complexity involved, catheter ablation supported by VA-ECMO is infrequently performed. We sought to assess the safety and effectiveness of emergent catheter ablation procedures performed in patients on VA-ECMO at our hospital. Methods: Retrospective study of all ventricular tachycardia (VT) catheter ablation procedures performed with VA-ECMO support at a tertiary centre between 2016 and 2020. Follow-up data was obtained from review of electronical records. Results: Five patients underwent 6 emergent VT ablation procedures due to AS. The median age was 62 years (range, 52) and 4 patients were men. Three patients had VT at admission, while 2 were admitted with an acute coronary syndrome and developed VT during the hospitalization. Four patients had ischemic heart disease, though only 1 had previous history of VT; the remaining patient presented no structural heart disease. Median left ventricle ejection fraction was 11% (range 30). All patients had incomplete response to amiodarone, lidocaine or overdrive pacing, before being proposed to catheter ablation. Four patients were on ECMO support before ablation, while 1 was cannulated during the procedure due to hemodynamic instability. Ablation was performed using a retrograde approach in 3 patients, and combined retrograde and transeptal access in 2; one patient had epicardial ablation after unsuccessful endovascular approach. Three patients had left ventricle substrate ablation and the remaining 2 of the right ventricle. No major complications were seen directly related to the procedures. The median length of stay in intensive care unit was 22 days (range 41 days). Weaning of VA-ECMO was accomplished in all patients. Two patient died during the same hospitalization (one due to uncontrolled arrhythmic events). At a median 23 months (range 31) of follow-up of the surviving patients, two had recurrence of VT but no one had return of AS. Conclusion: In our sample VT ablation on VA-ECMO support was a safe procedure, with no immediate complications. However, as reported in the literature, a high mortality rate was observed both in-hospital and during follow-up, mostly related to advanced structural heart disease. Also, considerable VT recurrence rates were seen, but with no re-hospitalization. Our experience shows that catheter ablation is a life-saving procedure in otherwise uncontrollable AS and allowed absolute success in weaning VA-ECMO. Funding Acknowledgement: Type of funding sources: None.